Pandangan Kepala KUA Di Kabupaten Jombang Terhadap Kedudukan dan Hak Anak Hasil Pernikahan Poligami Siri - Binabi Muhammad, Ittaba’a (ILJ: Islamic Learning Journal, 2025)
This article was written to determine the views of the Head of the Religious Affairs Office (KUA) in Jombang Regency regarding the status and rights of children born from unregistered polygamous marriages, as well as the implementation of legal protection. This study used a qualitative method with a case study approach in three subdistricts, namely Mojowarno, Jogoroto, and Ngoro. Data collection techniques included interviews, documentation, and observation, with descriptive qualitative data analysis techniques. The results of the study show that the head of the KUA considers the registration of marriages to be important as a condition for ensuring legal certainty for children born of siri polygamous marriages. Children born from siri marriages tend to only have civil relations with their mothers, while other rights such as inheritance and identity are often hampered due to the absence of legal evidence. The head of the KUA stated that marriages without registration have an impact on the status of the child's lineage, which can only be attributed to the mother, and this causes administrative difficulties and weak legal protection. In addition, many people still misunderstand siri marriages, without considering their validity in terms of sharia and formal legal aspects of the state. This study recommends increasing public legal awareness and synergy between religious law and state law to comprehensively guarantee children's rights.